Targeting Bcl-2 Proteins in Acute Myeloid Leukemia - Wei, Yunxiong; Cao, Yaqing; Sun, Rui; Cheng, Lin; Xiong, Xia; Jin, Xin; He, Xiaoyuan; Lu, Wenyi; Zhao, Mingfeng (Frontiers in Oncology, 2020)
B-cell lymphoma 2 (BCL-2) family proteins play an important role in intrinsic apoptosis. Overexpression of BCL-2 proteins in acute myeloid leukemia can circumvent apoptotic and chemotherapy resistance. Within this background, exploration in antiapoptotic BCL-2 inhibitors were considered to be a tremendous potential toward the discovery of novel pharmacological modulators in cancer. This review outlines the impact of the BCL-2 family proteins on intrinsic apoptosis and the development in AML. Furthermore, we will also review the new combination with venetoclax to overcome resistance to venetoclax and the biomarkers of response identified from the early phase clinical trials performed.